Tyrosinemia type 1: A case report - Prabhakar, Shashikala; Banu, Nasima; Meghana, S (Indian Journal of Child Health, 2014)
Tyrosinemia Type 1 is a rare inherited metabolic disorder attributable to a deficiency of enzyme fumarylacetoacetate hydrolase. It has an autosomal recessive pattern of inheritance. The accumulation of tyrosine and its toxic metabolites succinylacetone and succinyl acetoacetate in various tissues leads to the characteristic hepatic failure, renal dysfunction, and neurological crisis. Here, we present a case of a 7-month-old female infant who was brought with complaints of jaundice, dyspnea, altered level of consciousness, refusal to feed. We highlight the need for early diagnosis, including prenatal testing and initiating treatment at the earliest, which goes a long way not only in the survival, but also the quality of life in these patients.